• Matéria: Matemática
  • Autor: Aliciatereza156
  • Perguntado 5 anos atrás

( +2 ) • ( -6 ) + ( -5 ) • ( -3 ) =​


ehaeducacao: (+2) *(-6) + (-5) * (-3) =
ehaeducacao: -12 + (-5) * (-3) =
ehaeducacao: -12+15 =
ehaeducacao: = 3
ehaeducacao: a multiplicação de um número positivo por um numero negativo resulta em um número negativo: (+)*(-)=(-). (+2)*(-6) = -12
Aliciatereza156: obrigadaaaa ❤❤❤

Respostas

respondido por: NiceBurner
0

Resposta:

(+2)\cdot(-6)+(-5)\cdot(-3)=

(-12)+(+15)=

\white{\boxed{\pink{\boxed{3}}}

Explicação passo-a-passo:

Perguntas similares